COVID-19 disease induced alteration of oxidative stress and clinical laboratory parameters in moderate and severe patients - Zendelovska, Dragica; Petrushevska, Marija; Atanasovska, Emilija; Spasovska, Katerina; Gjorgjievska, Kalina; Pavlovska, Kristina; Grozdanovski, Krsto (My University, 2022)
The aim of our study was to present the clinical alterations of CRP, LDH, neutrophil to lymphocyte ratio, platelets to lymphocyte ratio, D-dimer, blood gas analyses, vitamin D, VEGF, IL-6, IFN-γ, CD4+, CD8+) and their correlation with oxidative stress index (OSI) in hospitalized COVID-19 patients.